Evaluation of the ETV success score to improve decision making on the management of hydrocephalus secondary to pediatric posterior fossa tumors: A feasibility study - Leopoldo Mandic Furtado; José Aloysio da Costa Val Filho; Aieska Kellen Dantas dos Santos; Jaime Xavier de Oliveira Neto; Márcio Júnior Pena; Cristiano Frattesi Bernardes; Mariana Gonçalves Lima de Paula; Anne Ribeiro Magalhães; Alice Izabel Costa Silva (Brazilian Society for Pediatric Neurosurgery, 2023)
Introduction: Hydrocephalus is frequently seen in children with posterior fossa tumors (PFT), and endoscopic third ventriculostomy (ETV) prior to tumor resection can improve surgical conditions by treating the hydrocephalus. Moreover, a scoring system predicting the success of ETV could aid in decision-making for this procedure. Objective: This study aims to evaluate the efficacy of ETV in the treatment of hydrocephalus related to PFT and to evaluate the accuracy of the ETV success score in predicting ETV success. Methods: Patients under 18 years of age who underwent ETV before PFT resection between 1996 and 2021 were included in a retrospective study. The ETV success score was retrospectively obtained for all patients, and its predictive capacity was compared to the actual success observed. Results: Of the 59 surgical cases, a global success rate of 62.7% was observed in the first 6 months following ETV. This rate dropped to 50.8% for those patients reassessed one year after surgery. There was no correlation between the success rate and the histological grade of the tumor or the age of the patient. The ETV success score presented acceptable accuracy at both time points (AUC = 0.671 at 6 months, AUC = 0.649 at one year). Conclusion: ETV proved be a safe procedure, capable of treating hydrocephalus in patients with PFT, and the ETV success score is useful for indicating probable success of the endoscopic procedure.